The Development of Innovation in Educational Video Media to Promote Awareness and Understanding of Ice Hockey in Thailand - สิริไพโรจน์ ปิยวัฒน์; เพ็ชรเขียว ณัฐณิชา; ดีเจริญชิตพงศ์ จิรวิญญ์ (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 16, 2026)
The research titled The Development of Innovative Educational Video Media to Promote Awareness and Understanding of Ice Hockey in Thailand aims to produce and disseminate educational video media about ice hockey in Thailand. Although ice hockey is widely popular in many countries, it is not yet well recognized in Thailand. Therefore, the development of video media is considered an effective approach for providing fundamental knowledge, rules, and benefits of the sport, as well as promoting positive attitudes toward exercise and sports participation. This study employed a systematic production cycle methodology, consisting of content analysis, media design, video production, expert evaluation, and revision. The sample group consisted of 30 youths aged 8–18 years who were interested in ice hockey. Data were collected through expert evaluation forms and satisfaction questionnaires using a 5-point Likert scale. The results revealed that the content quality evaluation by content experts achieved an overall mean score of 4.80, indicating the highest level of quality. The media quality evaluation by media experts obtained an overall mean score of 5.00, also reflecting the highest level of quality. Furthermore, the satisfaction evaluation of the sample group resulted in a mean score of 4.80, indicating the highest level of satisfaction.